Hike : adventures on foot - Laidler, Rachel (DK Publishing, 2022)
Compiled by a team of outdoor enthusiasts, this book is packed with ideas for your next hiking trip. Awe-inspiring images and compelling descriptions of each trail will have you itching to get walking, while handy maps, elevation profiles, and practical information -- including things like distance and total elevation gain-- will help you plan the nitty-gritty of your trip. We've also included the best places to explore en route -- whether that's lunch spots, epic viewpoints, or nearby must-see sights -- as well as suggestions for alternative ways to tackle a trail. Hike is your ticket to the adventure of a lifetime.--